Trends in evolution of the Rhodniini tribe (Hemiptera, Triatominae): experimental crosses between Psammolestes tertius Lent & Jurberg, 1965 and P. coreodes Bergroth, 1911 and analysis of the reproductive isolating mechanisms - Ravazi, Amanda [UNESP]; de Oliveira, Jader [UNESP]; Campos, Fabricio Ferreria [UNESP]; Madeira, Fernanda Fernandez [UNESP]; dos Reis, Yago Visinho [UNESP]; de Oliveira, Ana Beatriz Bortolozo [UNESP]; de Azeredo-Oliveira, Maria Tercília Vilela [UNESP]; da Rosa, João Aristeu [UNESP]; Galvão, Cleber; Alevi, Kaio Cesar Chaboli [UNESP] (Springer Nature, 2021)
Background: The tribe Rhodniini is a monophyletic group composed of 24 species grouped into two genera: Rhodnius and Psammolestes. The genus Psammolestes includes only three species, namely P. coreodes, P. tertius and P. arthuri. Natural hybridization events have been reported for the Rhodniini tribe (for genus Rhodnius specifically). Information obtained from hybridization studies can improve our understanding of the taxonomy and systematics of species. Here we report the results from experimental crosses performed between P. tertius and P. coreodes and from subsequent analyses of the reproductive and morphological aspects of the hybrids. Methods: Crossing experiments were conducted between P. tertius and P. coreodes to evaluate the pre- and post-zygotic barriers between species of the Rhodniini tribe. We also performed cytogenetic analyses of the F1 hybrids, with a focus on the degree of pairing between the homeologous chromosomes, and morphology studies of the male gonads to evaluate the presence of gonadal dysgenesis. Lastly, we analyzed the segregation of phenotypic characteristics. Results: Interspecific experimental crosses demonstrated intrageneric genomic compatibility since hybrids were produced in both directions. However, these hybrids showed a high mortality rate, suggesting a post-zygotic barrier resulting in hybrid unviability. The F1 hybrids that reached adulthood presented the dominant phenotypic segregation pattern for P. tertius in both directions. These insects were then intercrossed; the hybrids were used in the cross between P. tertius ♀ × P. coreodes ♂ died before oviposition, and the F1 hybrids of P. coreodes ♀ x P. tertius ♂ oviposited and their F2 hybrids hatched (however, all specimens died after hatching, still in first-generation nymph stage, pointing to a hybrid collapse event). Morphological analyses of male gonads from F1 hybrids showed that they did not have gonadal dysgenesis. Cytogenetic analyses of these triatomines showed that there were metaphases with 100% pairing between homeologous chromosomes and metaphases with pairing errors. Conclusion: The results of this study demonstrate that Psammolestes spp. have intrageneric genomic compatibility and that post-zygotic barriers, namely unviability of hybrid and hybrid collapse, resulted in the breakdown of the hybrids of P. tertius and P. coreodes, confirming the specific status of species based on the biological concept of species. Graphical abstract: [Figure not available: see fulltext.]
Keywords: Hybrid collapse; Hybridization; Hybrid’s unviability; Psammolestes genus; Triatomines